Hepatocyte Growth Factor in Patients with Three Different Stages of Chronic Liver Disease including Hepatocellular Carcinoma, Cirrhosis and Chronic Hepatitis: An Immunohistochemical Study - Banu Bilezikçi; Asuman Nihan Haberal; Beyhan Demirhan (Canadian Journal of Gastroenterology)
BACKGROUND AND AIMS: The specific role of hepatocyte growth factor in liver disease is unknown. The presence and density of this factor in patients with three different stages of liver disease were investigated, with the aim of assessing its prognostic significance.